Evolutionary ecology of masting: mechanisms, models, and climate change - Bogdziewicz, M.; Kelly, D.; Ascoli, D.; Caignard, T.; Chianucci, F.; Crone, E.; Fleurot, E.; Foest, J.; Gratzer, G.; Hagiwara, T.; Han, Q.; Journe, V.; et al. (My University, 2024)
Many perennial plants show mast seeding, characterized by synchronous and highly variable reproduction across years. We propose a general model of masting, integrating proximate factors (environmental variation, weather cues, and resource budgets) with ultimate drivers (predator satiation and pollination efficiency). This general model shows how the relationships between masting and weather shape the diverse responses of species to climate warming, ranging from no change to lower interannual variation or reproductive failure. The role of environmental prediction as a masting driver is being reassessed; future studies need to estimate prediction accuracy and the benefits acquired. Since reproduction is central to plant adaptation to climate change, understanding how masting adapts to shifting environmental conditions is now a central question.
Keywords: climate change; plant demography; economies of scale; environmental prediction; plant reproduction